Kemitraan LPKA Kelas II Bandung dengan Instansi Eksternal dalam Meningkatkan Kesadaran Hukum Anak Binaan: Penelitian - Syakila Ratubalqis Parawangsa Diputri; Dadang Sundawa; Asep Mahpudz (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The research aims to analyze the structure of partnerships formed, the implementation of development programs through such collaborations, and the readiness of foster children to engage with these programs. Employing a qualitative approach and a case study method, data were collected through in-depth interviews, participatory observation, and documentation review. The findings reveal that partnerships with external institutions, such as the Child Rights Advocacy Institute (LAHA), are mutualistic in nature, grounded in principles of equality, transparency, and mutual benefit. The rehabilitation programs include skills training, religious education, legal counseling, and psychosocial support, guided by social learning theory. The readiness of foster children is influenced by both internal factors (motivation, self-awareness) and external factors (supportive environment, program delivery), which in turn affect behavioral changes, increased discipline, and active participation. These findings offer critical recommendations for strengthening partnership-based child rehabilitation programs that are aligned with the goals of civic education and social reintegration.